HUBUNGAN AKSES PELAYANAN, KEAKTIFAN IBU DAN KEPERCAYAAN IBU TERHADAP KETEPATAN PEMBERIAN IMUNISASI DASAR - Shinta Mona Lisca; Puspita Sari Winarya (Poltekkes Kemenkes Maluku, 2023)
Basic immunization is an immunization that is required to be given to babies before they are one year old in order to protect babies from disease. In PMB A in 2021 as many as 528 babies will receive complete basic immunization. This research aims to knowrelationship between service access, mother's activeness and mother's trust in the accuracy of basic immunization at pmb a bogor district in 2022. The research design used cross sectional.A sample of 90 respondents used probability sampling technique. The research instrument used a questionnaire. Data analysis using univariate and bivariate. The results showed that 32.2% of respondents were inappropriate in giving immunizations, 41.1% of respondents had access to services far from the place of immunization, 38.9% of respondents were not active, 47.8% of respondents did not believe. There issig relationshipnegativity between service access(p=0.005) and mother's trust(p=0.02)on the accuracy of deliveryImmunization at PMB A, Bogor Regencyyear 2022and variables that are not related to mother's activity (p=0.055). The accuracy of giving basic immunization is influenced by access to services and mother's trust. It is hoped that mothers who have babies can bring their babies to the nearest health service place to be given basic immunizations at the right time to obtain good health welfare for their babies. Mothers can be more motivated in seeking information from health workers, the internet and family and closest people regarding timely administration of basic immunization.